Analisis Profesionalisme Kerja terhaap Tatakelola Keuangan Sekretariat Daerah Kota Medan - Lubis, Nurul Rafiqoh; Arif, Muhammad (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Professional arrangement of apparatus resources must be prioritized, because reforms in the field of government administration expect the presence of a government that is more qualified and capable of carrying out public service functions. The focus and hope is directed at the government apparatus, because the government apparatus is the provider of services for the community as well as the person in charge of the function of public services in Indonesia which directs its goals to public service, thinks about and seeks to achieve service goals for the entire community in various layers. This research was conducted as one of the outputs of the Field Practice Program (internship) which was carried out for one month at the Medan City Regional Secretariat Office. The research method used in this study is a qualitative descriptive method. The type of data used in this study is primary data, which collects data by observing customers and directly interviewing employees of the Medan City Regional Secretariat. The results of this study are that even though they consist of different educational backgrounds, and in work positions that are not in accordance with their educational background, the work is still carried out properly according to their duties and functions and follows the basic accounting equation system as the basis for managing finances at the Secretariat. Medan City area.